ANTIOXIDANT EFFECT OF ANT EFFECT OF ANT EFFECT OF TINOSPORA CORDIFOLIA STEM EXTRACT IN STREPTOZOTOCIN INDUCED DIABETIC RATS - A. MOHAMED SADIQ,; R. S. VENKATESAN,; V. SIVA KUMAR,; G. YOGANANTHARAJ, (The Bioscan, 2009)
Many drugs commonly used today are of herbal origin. About 25% of the prescription drugs dispersed in the India contains at least one active ingredient derived from plant material as plant extract due to side effect free nature and antioxidant activity. In this present study Tinospora cordifolia was used to treat Diabetes mellitus which is an endocrine disorder characterized with hyperglycemic and free radical production. The obtained results revealed intake of Tinospora cordifolia stem extract at the dose of 500mg/kg body weight increase the antioxidant activity.